1997
DOI: 10.1046/j.1365-2672.1997.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Phages of enteric bacteria in fresh water with different levels of faecal pollution

Abstract: Levels of somatic and F-specific coliphages, and phages infecting Bacteroides fragilis were measured in 257 samples collected in different freshwater environments with different levels and characteristics of faecal pollution. In samples with recent pollution of domestic origin, the numbers of the three groups of phages were highly correlated, thus showing that their excretion is fairly constant. In this set of samples somatic coliphages, which were the most abundant, and F-specific coliphages outnumbered signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 3 publications
(5 reference statements)
4
25
0
2
Order By: Relevance
“…This suggests that the effect of sedimentation on removal is similar for all the micro-organisms studied. Although few reports have examined the sedimentation of the various micro-organisms in river water, our results are consistent with the data available for sedimentation of bacteriophages in sewage or very polluted waters (Araujo et al 1997), which indicate that the three groups of bacteriophages sediment similarly. Moreover, all of these data, together with the numbers of micro-organisms in river area A, in which no inactivation was detected, indicate that the reduction in bacterial indicators and bacteriophages in river water was a slow process.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that the effect of sedimentation on removal is similar for all the micro-organisms studied. Although few reports have examined the sedimentation of the various micro-organisms in river water, our results are consistent with the data available for sedimentation of bacteriophages in sewage or very polluted waters (Araujo et al 1997), which indicate that the three groups of bacteriophages sediment similarly. Moreover, all of these data, together with the numbers of micro-organisms in river area A, in which no inactivation was detected, indicate that the reduction in bacterial indicators and bacteriophages in river water was a slow process.…”
Section: Discussionsupporting
confidence: 90%
“…The behaviour of bacteriophages in nature has been compared with that of viruses and bacterial indicators elsewhere (Bell 1976;Payment et al 1988;Gironés et al 1989;Moriñigo et al 1992;Chung and Sobsey 1993;Araujo et al 1997;Jofre et al 2000). However, few of these reports contain data on the complete set of bacterial and bacteriophage indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Although in the sandy sediments the number of somatic coliphages outnumbered the F-specific phages, which is in agreement with previous results (Araujo et al 1997), in clayey sediments, the opposite was observed.…”
Section: Discussionsupporting
confidence: 82%
“…Such phenomena may partly explain seasonal (9) and geographical differences in the indicator content in bivalves. For example, strains of bacteriophages infecting B. fragilis have been shown to be useful as enteric viral indicators in some geographical areas, such as South Africa and Southern Europe (4,5,21) but, e.g., not in the United States (31).…”
mentioning
confidence: 99%